Karakteristik Penderita Adenokarsinoma Paru Di RSUD Dr. H. Abdul Moeloek Lampung Periode Tahun 2014-2019 - Trixie Almira; Rizki Hanriko; Ari Wahyuni; Retno Ariza Soeprihatini (Majority, 2023)
Adenonacarcinoma of the lung is the largest type of lung carcinoma. Risk factors of lung adenocarcinoma are include age, gender and smoking history. Lung adenocarcinoma therapy generally consists of chemotherapy and developed targeted therapy, such as targeting genes that activate proliferation such as Epidermal Growth Factor Receptor (EGFR). The research is a descriptive and observational analytic study with a cross sectional approach. The number of samples obtained was 82 samples obtained using the Total Random Sampling technique. Analyze descriptive statistical test results showed that most patients with lung adenocarcinoma were found in the 40-60 years age group (61.0%), the most sex was found in men (64.6%), had a history of smoking (54.9%), some large were diagnosed at stage IV (80.5%), there was no EGFR gene mutation (54.9%), and had survival rate > 1 year diagnosed (62.2%). The results showed a relationship between gender (p value = 0.040), smoking history (p value = 0.002), survival rate (0.012) with EGFR gene mutations. Meanwhile, there was no significant corelation between sex (p value = 0.448) and the EGFR gene mutation. Lung adenocarcinoma is most commonly found in males in the adolescent age group of 40-60 years with a history of smoking, stage IV, no EGFR gene mutation and survival rate >1 year and there is an association between sex, smoking history, survival rate with EGFR gene mutations in patients lung adenocarcinoma.